2007
DOI: 10.1002/pmh.21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personality and personality disorders on the treatment of depression

Abstract: It is well known that the presence of personality disorder presents special challenges in the treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…From a clinical perspective, it is relevant to achieve knowledge both of the vulnerabilities that underlies symptomatology (in this case, personality functioning) and of the risk factors, especially the ACE. This, in order to be able to make an approach that not only addresses the current symptomatic manifestation of the patient, but also takes a complete look at its complexity and heterogeneity, including interventions that are conducive to the patient's profile, enriching an idiosyncratic and patient-centered treatment (Van Praag, 1989;Gabbard and Simonsen, 2007;Dagnino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, it is relevant to achieve knowledge both of the vulnerabilities that underlies symptomatology (in this case, personality functioning) and of the risk factors, especially the ACE. This, in order to be able to make an approach that not only addresses the current symptomatic manifestation of the patient, but also takes a complete look at its complexity and heterogeneity, including interventions that are conducive to the patient's profile, enriching an idiosyncratic and patient-centered treatment (Van Praag, 1989;Gabbard and Simonsen, 2007;Dagnino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Depressions differ depending on the patient's personality, among other factors (Gabbard & Simonsen, 2007), so that the interrelationship between depressive symptoms and personality have important implications for treatment. Empirical studies have shown the magnitude of treatment effects are moderated by a variety of primary manifestations of personality organization -including pre-treatment levels of personality pathology (Koelen et al, 2012); attachment style (Diener & Monroe, 2011); degree of object relations (Piper, McCallum, Joyce, Rosie, & Ogrodniczuk, 2001); alexithymia (Ogrodniczuk, Piper, & Joyce, 2011); and selfcriticism (Blatt, Zuroff, Hawley, & Auerbach, 2010).…”
Section: Personalitymentioning
confidence: 99%
“…(Luyten & Blatt, 2013, p. 175) Empirical studies have demonstrated distinct patterns of change in anaclitic and introjective patients (Blatt, 1995;Blatt & Ford, 1994;Blatt, Ford, Berman, Cook, & Meyer, 1988;Blatt, Sanislow, Zuroff, & Pilkonis 1996;Blatt & Shahar, 2004;Blatt, Zuroff, Bondi, Sanislow, & Pilkonis, 1998;Gabbard & Simonsen, 2007;Vermote et al, 2009Vermote et al, , 2011. However, no previous study has explored the change in degree of anaclitic -introjective organisation over treatment (Blatt, personal communication, 2 May 2013).…”
mentioning
confidence: 96%